Manejo Integrado de pudrición de la flecha en el cultivo de palma aceitera (Elaeis guineensis Jacp) en Ecuador - Ledezma Cellan, Edwin Bolívar (2019)
Historically, phytosanitary programs have had unwanted impacts on agroecosystems, so the identification of these in their different dimensions is considered a necessity. Currently, Integrated Pest Management (IPM) is not only limited to technical aspects, but also encompasses social aspects, which allows a broader concept that has technicians and producers as the main focus. In this new context, information and knowledge play a fundamental role as an essential component of IPM in the cultivation of oil palm, especially with the appearance of arrow rot. This work was developed with the objective of determining the state of the art based on the IPM on the incidence of arrow rot and developing a compilation of information with the objective of documenting sustainable management strategies